Speeding up Lgbtq+ talent - how can management consulting firms recruit with meaning and inclusiveness - Ferreira, Pedro Santos (2023)
This Work Project extends the research conducted for a CEMS Business Project focused on recruiting female talent at McKinsey Portugal. Building on this foundation, the focus shifts to examine the inclusiveness of the management consulting industry for LGBTQ+ individuals, while offering recommendations on how to effectively recruit this talent pool. Through interviews, the study emphasizes the importance of authenticity, transparency, and action in communication efforts, along with providing platforms for LGBTQ+ voices and actively publicizing inclusion initiatives. By implementing these recommendations, management consulting firms can reshape their perceptions and successfully attract LGBTQ+ talent while fostering diversity, equity, and inclusion.